Use of the Herbicide Glyphosate in Costa Rica Between 2007-2015 - Ramírez-Muñoz, Fernando; Bravo-Durán, Virya; Herrera-Ledezma, Gustavo (Uniciencia, 2017)
Costa Rica is one of the largest importers and users of pesticides in Central America. Glyphosate is the most widely used herbicide worldwide as in Costa Rica. It is used in most crops, both annual and perennial and in non-agricultural areas. The glyphosate amounts used on major crops in Costa Rica became known through interviews with farmers. Costa Rica started importing this herbicide in 1982 with 36 tons of active ingredient (T ai) reaching in 2013 the amount of 1,761 T ia. The weighted average use of glyphosate in kg ai / ha / cycle was calculated. The perennial crops are the main consumers of glyphosate (51.6% of the total), followed by non-agricultural areas (37.1%) and annual crops (10.8%) most grains like rice, beans and corn. By culture, African palm consume 24.9% of glyphosate used in the country, followed by rice (7.8%), coffee (5.4%), bananas (5.2%), citrus fruits (4.6%) and pastures (3.7%). In some crops, such as hearth-palm trees, a dependency on this herbicide in weed management has led resistant weed populations to evolve.